PENGANGKATAN DEWAN KOMISARIS DAN DIREKSI BANK MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 1992 JO. UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN - Bismar Nasution; Windha Windha (Universitas Sumatera Utara, 2014)
One of the efforts that can be made to produce a good management structure is via a selection process of the owner and board of management (the board of commissioners and board of directors) on all the banks that carried through to test the ability and propriety (fit and proper test). Appointment of board of commissioners and board of directors of the bank are regulated in the banking act. However, during this appointment of board of commissioners and board of directors of the bank comply with the